2012
DOI: 10.1080/19371918.2011.542975
|View full text |Cite
|
Sign up to set email alerts
|

Policy Implications of Medicare Part D for Adults With Mental Illness: A Qualitative Exploration

Abstract: The Medicare prescription drug benefit, introduced in January 2006, has had a substantial impact on the lives of adults disabled by mental illness. However, few studies have undertaken an exploration of the difference that this benefit has made to beneficiaries' access to medication. This study uses a qualitative approach to examine beneficiaries' experiences with the Medicare Part D benefit, and whether having Medicare prescription drug coverage is perceived as helpful. Twenty-six Medicare beneficiaries with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The few studies on this population found mixed outcomes, which could be due to the small and nonrepresentative samples (Millett et al. ; Hensley ). Future research with representative samples is needed to evaluate effects on dual‐eligibles with various health conditions and level of prescription drug spending.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The few studies on this population found mixed outcomes, which could be due to the small and nonrepresentative samples (Millett et al. ; Hensley ). Future research with representative samples is needed to evaluate effects on dual‐eligibles with various health conditions and level of prescription drug spending.…”
Section: Discussionmentioning
confidence: 94%
“…), dual‐eligibles did not have higher OOP costs. A qualitative study of adults with mental illness found mixed perceptions about the impact on OOP costs, with some interviewees expressing that Medicare Part D premiums and copayments were reasonable, while others revealing them to be a significant burden preventing them from obtaining other necessities (Hensley ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, an increase in this copayment in 2005 led to decreased dispensings of some essential drugs; an unwanted feature of a limited copayment policy [23]. Some American qualitative studies have been carried out, however, they were focused on the logistical challenges that patients were faced with when Medicare Part D was established,[24] concentrated on how patients managed their medicines when taking multiple drug regimens [25] or were concerned solely with the opinions of mental health patients [26]. Even though there is an extensive literature available on the quantitative effects of copayments, and how this varies according to price paid and medicines used, there is a limited qualitative literature on examining public attitudes to small copayments.…”
Section: Introductionmentioning
confidence: 99%